Clinical manifestations and immunological parameters post-COVID-19 in unvaccinated pediatric patients - Julio César Francisco Pérez; Mileny Piedra Garcés; Claudia Ruiz Mármol; Ernesto Rogelio García Montalvo (Universidad de Ciencias Médicas de La Habana, 2023)
Introduction: Given the COVID-19 pandemic, consultations are established to monitor convalescent children and adolescents in order to prevent, detect and treat alterations caused by the virus. Objective: To describe the clinical manifestations and immunological parameters in unvaccinated pediatric patients after COVID-19 disease at the "Borras-Marfan" Pediatric Hospital from July 2021 to July 2022. Material and Methods: A descriptive, longitudinal and prospective investigation was carried out in 48 unvaccinated patients, aged between 0 and 18 years, of both sexes, and receiving care in a post-COVID-19 follow-up consultation. Demographic variables, blood typing, clinical classification of the disease, Post-COVID-19 clinical manifestations, and evaluation of immunity were studied. Descriptive statistics was used and a multivariate analysis was performed using the statistical technique: multiple correspondence analysis. Results: Patients from the age group of 1 to 4 years (54.2%) and blood type O+ (54.2%) predominated. The main clinical classification was mild (66.7%); however, 72.9% presented post-COVID-19 clinical manifestations and 14.3% of them maintained symptoms after 12 weeks. Blood type O+ was associated with mild disease and no post-COVID-19 manifestations. Also, 79.9% of the patients had immune deficiency. Conclusions: Most patients presented mild disease although they had alterations in humoral and cellular immunity, which is why a group of them remains under surveillance and treatment.